THE PORTRAITS OF TEACHING STUDENTS WITH SPECIAL NEEDS IN TAARE ZAMEEN PAR MOVIE - Safira Udin; Naniek Jusnita; Silvani Umar Ali (Universitas Khairun, 2022)
This thesis examines teaching students with special needs in Aamir Khan movie â€œTaare Zameen Parâ€. This thesis examines teaching student with special needs in Aamir Khan movie â€œTaare Zameen Parâ€. The purpose of this thesis is to describe what are teaching method used to teach student with special needs the type of dyslexia in the movie taare zameen par. This research is qualitative research design with a descriptive. The data is collected through analysis document and to be analyzed using content analysis. The results show that teachers who teach children with special needs use a variety of media to stimulate children's learning by using the VAKT multisensory method.The multisensory method is a learning method that utilizes the functions of each sense. The multisensory method is based on the assumption that students will learn better if the subject matter is presented in a variety of modalities. The modalities that are often involved are visual (vision), auditory (hearing), kinesthetic (movement), and tactile (touch) called (VAKT). The stages of teaching using the multisensory VAKT method carried out by the teacher in Aamir Khan's film consist of several stages, namely: (1) The Visual stage in the scene (9, 11, 13), (2) The Auditory stage in the scene (12, 14, 15), (3) Kinesthetic Stage in scene (16), and (4) Tactile Stage in scene (10). This method can generate new desires and interests in students, generate motivation, provide stimulation for learning activities, and even bring psychologicaleffects on students which ultimately increase students' concentration to learn and understand lessons. Thus this method can assist in the implementation of learning for children with special needs and in the future there will be no more children with special needs who have difficulty in learning.